Bemba. (30th March 2015) - Hamann, Silke; Kula, Nancy C.
Abstract : Bemba (also called Cibemba or Icibemba; ISO 639-3 code bem ) is a Niger-Congo language belonging to the Central Narrow Bantu branch (Zone M in Guthrie's1948, 1967–71 classification). Bemba is spoken in Zambia (mainly in the Northern, Luapula and Copperbelt provinces) and the Southern Democratic Republic of Congo by approximately 3.3 million speakers (Lewis, Simons & Fennig2013 ). Our data are based on Bemba spoken in Zambia.